LINC01614 Promotes Colorectal Cancer Cell Growth and Migration by Regulating miR-217-5p/HMGA1 Axis - Jiwei Jia; Pei Guo; Li Zhang; Wenqing Kong; Fangfang Wang (Analytical Cellular Pathology, 2023)
Colorectal cancer (CRC) substantially contributes to cancer-related deaths worldwide. Recently, a long non-coding RNA (lncRNA), LINC01614, has emerged as a vital gene regulator in cancer progression. Yet, how LINC01614 affects CRC progression remains enigmatic. Here, we defined LINC01614 expression in CRC, investigated the performance of CRC cells lacking LINC01614, and elucidated the underpinning mechanism. We observed that LINC01614 was upregulated in both CRC tissues and cell lines. LINC01614 knockdown repressed the proliferation and metastasis capacity of CRC cell lines. Consistently, an in vivo LINC01614 deficiency model exhibited slow tumor growth rate. Moreover, luciferase reporter assay, RNA pull-down, and immunoprecipitation confirmed that LINC01614 targeted miR-217-5p. LINC01614 knockdown reduced the expression of HMGA1 and N-cadherin, while increasing that of E-cadherin, resulting in decreased viability, proliferation, migration, and invasion capacity of CRC cells. Our results demonstrate that LINC01614 regulates CRC progression by modulating the miR-217-5p/HMGA1 axis, thus holding great potential as a prognostic biomarker for CRC diagnosis and treatment.